Male Hypogonadism After Recovery from Acute COVID-19 Infection: A Prospective Observational Study - Prasad, Aravind; Rashmi, K G; Sahoo, Jayaprakash; Kamalanathan, Sadishkumar; Wyawahare, Mukta; Anusuya, R; Naik, Dukhabandhu (Experimental and clinical endocrinology & diabetes, 2024)
The severe acute respiratory syndrome coronavirus 2 can affect the hypothalamic-pituitary-gonadal axis (HPG) due to the expression of the angiotensin-converting enzyme 2 receptor. To assess the prevalence of hypogonadism and Sertoli cell dysfunction in coronavirus disease 2019 (COVID-19) male survivors. Male subjects recovered from acute COVID-19 infection were prospectively observed. The primary outcomes included the proportion of hypogonadism, defined biochemically as serum testosterone<230 ng/dL or CFT of<6.4 ng/mL if the total testosterone is between 230-320 ng/m. Sertoli cell dysfunction was defined as inhibin-B level<54.5 pg/mL. Subjects with hypogonadism were followed up at 12 months to assess the recovery of the HPG axis. Eighty-three subjects aged≥18 years were evaluated at a median of 120 (±35) days post-recovery. Their mean age was 49.50±12.73 years, and the mean BMI was 26.84±5.62 kg/m . Low testosterone was detected in 21 (24.71%) and low inhibin-B was detected in 14 (19.71%) out of 71 subjects at 3 months. Subjects with low testosterone were younger, with a mean age of 43.29±12.03 years (P-0.08) and higher BMI (P-0.012). The severity of COVID-19 infection, duration of hospitalization, and other factors were not significantly associated with low testosterone. At 12 months, 18 out of 21 subjects came for follow-up, of which 9 (50%) showed persistently low testosterone, suggestive of hypogonadism. Following COVID-19 infection, testosterone levels recovered over time; however, a significant proportion of subjects had low levels at 12-month follow-up. These findings have long-term implications for the management of COVID-19 subjects.